2009
DOI: 10.1158/1078-0432.ccr-09-0280
|View full text |Cite
|
Sign up to set email alerts
|

GAB2 Amplifications Refine Molecular Classification of Melanoma

Abstract: Purpose: Gain-of-function mutations in BRAF, NRAS, or KIT are associated with distinct melanoma subtypes with KIT mutations and/or copy number changes frequently observed among melanomas arising from sun-protected sites, such as acral skin (palms, soles, and nail bed) and mucous membranes. GAB2 has recently been implicated in melanoma pathogenesis, and increased copy numbers are found in a subset of melanomas.We sought to determine the association of increased copy numbers of GAB2 among melanoma subtypes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…It has been reported that NRAS and BRAF mutations are mutually exclusive (15,19). Interestingly, the case with the BRAF missense mutation had wild-type c-kit (13) suggesting that the c-kit mutation is independent from the BRAF mutation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that NRAS and BRAF mutations are mutually exclusive (15,19). Interestingly, the case with the BRAF missense mutation had wild-type c-kit (13) suggesting that the c-kit mutation is independent from the BRAF mutation.…”
Section: Discussionmentioning
confidence: 95%
“…NRAS and BRAF mutations have been reported in subsets of mucosal melanomas, but most reports focused on combined mucosal sites (9,(16)(17)(18)(19). Most reports have claimed that NRAS and BRAF mutations are infrequent, justifying that mucosal melanoma is distinct from its cutaneous counterpart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, although the BRAF gene is mutated in approximately 50% of melanomas from hair-bearing skin, BRAF is only mutated in approximately 16% of acral melanomas, and whereas KIT is not mutated in melanoma from hair-bearing skin, it is mutated in approximately 20% of acral melanomas (Curtin et al, 2006). Furthermore, focal gene amplifications involving the regions that encode GAB2 (Chernoff et al, 2009), CCND1 (Sauter et al, 2002) and CDK4 (Curtin et al, 2005) in particular appear to be more prevalent in acral melanoma than in hair-bearing skin melanoma. These studies have demonstrated that cutaneous melanomas from hair-bearing and acral skin are genetically distinct diseases, and accordingly, at least in some studies, it has been shown that acral melanoma is inherently more aggressive and has a poorer prognosis than melanoma from hair-bearing skin (Bradford et al, 2009).…”
mentioning
confidence: 99%
“…Among the 23 acral and mucosal melanomas studied, copy number changes in GAB2 were found in 26% and KIT in 13% (3 of 23) of the cases. Mutations in BRAF were identified in 30% (7 of 23) of the cases and NRAS, in 4% (1 of 23) of the cases (Chernoff et al, 2009).…”
Section: Cytogenetics Morphologicalmentioning
confidence: 99%